Pollen morphology of Boraginaceae s.l. from Brazilian forest fragments: aperture types and ornamentation on Cordiaceae and Heliotropiaceae - Landi, Lorrayne Albernaz Domingues Camilo; Torrati-Guioti, Paloma Gaspar; Gasparino, Eduardo Custódio [UNESP] (Taylor & Francis, 2021)
Boraginaceae s.l., the single family of Boraginales, are extremely diverse in terms of morphology, and their species are well distributed in South America especially in Brazilian ecosystems. The pollen morphology of 11 Brazilian native species and four genera (Cordia L., Varronia P. Browne, Heliotropium L. and Myriopus Small) of Boraginaceae s.l. was investigated to expand the morphological knowledge of the species, contributing new data on the palynology, taxonomy, and conservation of the family. The pollen grains were acetolyzed, measured, photographed using light microscopy (LM) and scanning electron microscopy (SEM), and described qualitatively. The analyzed species present differences in size, shape, type and number of apertures (3-porate, 3-colpate, 3-colporate and heterocolpate) and exine ornamentation (psilate, echinate, microechinate-verrucate, reticulate and rugulate) of the pollen grains, allowing the species studied to be distinguished. Multivariate analysis of measurements confirms the qualitative description and pollen diversity in Cordiaceae species. Smaller diameter values and similarities in aperture and exine ornamentation characterize the Heliotropiaceae species. Our data reinforce the taxonomic importance of pollen morphology and of Boraginaceae s.l. as eurypalynous.
Keywords: Cordiaceae; eurypalynous; Heliotropiaceae; palynotaxonomy; pollen grains